Development of Psychomotor Domain Assessment Instrument on Brake System Competence in SMKN 1 Jetis Mojokerto - Ariyanto, Sudirman Rizki; Munoto, Munoto; Muhaji, Muhaji (Universitas Malikussaleh, 2019)
Many factors influence the low number of skilled vocational high school graduates. One factor that is the leading cause is the lack of instruments that can be used in the learning process, especially authentic instruments, to assess students' abilities in the psychomotor domain. Students who are dominant in the cognitive sphere are not necessarily skilled in the psychomotor realm, especially when using the equipment and making improvements to the brake system. The purpose of this study is to develop an assessment instrument that is appropriate to be used by the teacher in evaluating the psychomotor domain's abilities, specifically for the brake system competency. This research is development research that uses ADDIE models as a reference for research. ADDIE model has five stages of development that need to be considered, including analysis; (2) design; (3) development; (4) implementations; and (5) evaluation. Based on the results of the analysis and discussion of the psychomotor domain assessment instrument for the competency of the brake system that was developed to be suitable for use in the learning process. Feasibility is proven from the results of the validation of experts who get an assessment of 4.66 with a very valid category. The instrument reliability test results that get the Cronbach's alpha value of 0.895, and the value of inter-observer reliability is 0.740. In addition, the instrument is also practical when used in the learning process. This was evidenced by the acquisition of practicality test value of 3.31 and entered in the practical category.